HYDROTHERMAL SYNTHESIS OF TRICOBALT TETRAOXIDE AND CHARACTERIZATION - Chaiya, Nuenghathai; Tapala, Weerinradah; Kunthadee, Phetlada; Ladrodphan, Nattapol; Tangkuaram, Tanin; Puntharod, Ratchadaporn (PSRU Journal of Science and Technology, 2024)
Tricobalt tetraoxide (Co3O4) was prepared in this work by hydrothermal method using cobalt (II) nitrate hexahydrate as a starting material and sodium hydroxide as a reducing agent in an equimolar ratio. The reaction mixture was heated at 180°C for 1, 3, and 5 hours. Then calcination was heated at 500°C for 5 hours. The functional group of Co-O bond was studied by Fourier transform infrared spectroscopy (FTIR)and appeared at 570 and 665 cm1. The morphology of the Co3O4 was studied by Scanning electron microscopy (SEM) which revealed the aggregated shaped like a rice grain in shape with an average particle size of 0.5 micrometers. The crystalline structure was studied by X-ray diffraction (XRD) technique. The Co3O4 was a cubic structure with a lattice constant, a = 8.1100 angstrom. The crystallite average sizes were 16.83, 19.12 and 20.84 nanometers, respectively. In the future, tricobalt tetraoxide will be utilized as an active ingredient to inhibit bacteria and fungi in plant pathogens.